PARK2 and PACRG are commonly downregulated in clear‐cell renal cell carcinoma and are associated with aggressive disease and poor clinical outcome. Issue 3 (2nd November 2012) - Toma, Marieta I.; Wuttig, Daniela; Kaiser, Sandy; Herr, Alexander; Weber, Thomas; Zastrow, Stefan; Koch, Rainer; Meinhardt, Matthias; Baretton, Gustavo B.; Wirth, Manfred P.; Fuessel, Susanne
Abstract PARK2 is an E3 ligase, known to be involved in ubiquitination of several proteins and to play a role in neuronal protection. The gene PARK2 and its potentially co‐regulated gene PACRG have been previously found to be deleted in clear‐cell renal cell carcinomas (ccRCCs). The aim of our study was to evaluate the mRNA and protein expression of PARK2 and PACRG in a large cohort of ccRCC, and to investigate their association with outcome. The expression of both genes was measured by quantitative PCR in 94 primary ccRCCs and autologous nonmalignant kidney tissues. PACRG and PARK2 protein expression was determined immunohistochemically using tissue microarrays comprising 133 ccRCCs. The mRNA and protein expression of PARK2 and PACRG was significantly downregulated in ccRCCs compared with nonmalignant tissues. Low levels of PARK2 mRNA were associated with high‐grade ccRCC and lymph node metastasis. Patients with low PARK2 mRNA levels showed a higher tumor‐specific mortality rate and a shorter overall survival (OS) than those with high PARK2 expression. Patients without PACRG mRNA expression in the tumor had a shorter disease‐free survival and OS than those with tumors expressing PACRG. In multivariate analyses, neither PARK2 nor PACRG expression were independent prognostic factors. The protein expression of PARK2 and PACRG was significantly downregulated in ccRCCs (82.8, and 96.9%, respectively), but no association with clinical outcome was noticed. © 2012 Wiley Periodicals, Inc.